(untitled) (Journal of Tropical Marine Science, 2023)
Matras Beach is one of the beach in the Bangka Belitung Archipelago used as a tourist destination. The coastline is the line that separates land and sea which can change every year. The aims of this study are to determine the change and rate of shoreline change before (2000-2010) and after the breakwater (2010-2020), and its impact on beach tourism at Matras Beach. The method used in this research is the digitization method and the Digital Shoreline Analysis System. The results showed that from 2000 to 2010, before the Matras Beach breakwater, there was a maximum increase of 34.23 m at a rate of 3.42 m/year and a maximum reduction of -35.10 m at a rate of -3.51 m/year, while after the breakwater in 2010-2020 Matras Beach experienced a maximum increase of 72.79 m at a rate of 7.28 m/year and a maximum reduction of -81.72 m at a rate of -8.17 m/year. This change resulted in 3.64 ha of abrasion and 1.50 ha of accretion before the breakwater and 8.48 ha of abrasion and 4.20 ha of accretion after the breakwater. This abrasion has a negative impact on beach tourism on Matras Beach because it will damage vegetation and buildings on the coast.